2009
DOI: 10.1354/vp.07-vp-0067-c-fl
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Evaluation of Vascular Urinary Bladder Tumors from Cows with Enzootic Hematuria

Abstract: Abstract. Fifty-six endothelial-derived urinary bladder tumor samples collected from 26 animals with bovine enzootic hematuria were selected for immunohistochemical studies. Expression of factor VIII-related antigen (FVIIIra), CD31, muscle-specific actin, uroplakin III (UPIII), and the cell cyclerelated proteins cyclin D1 and p53 was evaluated in hemangiomas, ''hemangioendotheliomas'' (a vascular tumor that histologically is intermediate in appearance between a hemangioma and a conventional hemangiosarcoma), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…The results obtained for p53 in muscle-invasive carcinomas are higher than what has been reported for the muscle-invasive stage hemangiosarcomas in BEH. 3 Mutation and deletion of the p53 tumor suppressor gene are considered the most frequent genetic alterations of bladder cancer in humans and are associated with advanced disease 8 and lower survival rates. 5 In conclusion, the present study showed that the expression of UPIII is lost in high-grade muscle-invasive bladder carcinomas of cows affected by BEH, while other structural proteins such as CK7 seem to be better retained in the process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained for p53 in muscle-invasive carcinomas are higher than what has been reported for the muscle-invasive stage hemangiosarcomas in BEH. 3 Mutation and deletion of the p53 tumor suppressor gene are considered the most frequent genetic alterations of bladder cancer in humans and are associated with advanced disease 8 and lower survival rates. 5 In conclusion, the present study showed that the expression of UPIII is lost in high-grade muscle-invasive bladder carcinomas of cows affected by BEH, while other structural proteins such as CK7 seem to be better retained in the process.…”
Section: Discussionmentioning
confidence: 99%
“…1,16,20 The expression of cyclin D1, a nuclear protein specifically involved in the G1/S phase transition, is frequently overexpressed in urothelial cancer in humans, 22 having been expressed in 100% of the hemangiosarcomas tested in bovine bladder tumors. 3 The alterations of the p53 pathway were identified as one of the most important events in the development of aggressive behavior in tumors. 10 Mutations of p53 are known to occur in 50% of human cancers, 24 including urothelial carcinomas.…”
mentioning
confidence: 99%
“…Some studies have explored the importance of establishing immunohistochemical cutoff values for the p53 positivity as an indirect indicator to distinguish wt from mutant p53, obtaining different results. Many immunohistochemical studies define a mutant protein as occurring when neoplasms show a nuclear immunoreaction for p53 in more than 10% of the tumour cells [4,18,21], while other studies chose a rate of more than 20% [29,31] or 40% [28,32,33] of the tumour cells as their cutoff value. The present study supports a p53 index > 38% as cutoff value because it was found in the 92.6% of tumours which were diagnosed as cutaneous HSAs based on the abnormal proliferation of cells and their histological characteristics of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Urinalysis did reveal struvite crystals and urine culture yielded light growth of Enteroccoccus sp. Other considerations for bladder masses in ruminants include exposure to environmental toxins, viral associated papilloma, and neoplasia 18–22 . Bovine papilloma virus Type 2 has been associated with development of bladder neoplasia in cattle especially when grazing bracken fern plants 19 .…”
Section: Discussionmentioning
confidence: 99%